A Demographic Portrait of Migrants From the Soviet and Post-Soviet Space in Eastern Hungary: A Preliminary Analysis of Questionnaire Data - Kisil, Oksana (Slavica, 2026)
Migration has accompanied humanity throughout its entire history, shaping cultures, economies, and social structures across regions. This study examines the demographic profile of migrants from Soviet and post‑Soviet states residing in Eastern Hungary, highlighting gender, age, timing of migration, and geographic origins. These characteristics illuminate the mechanisms of adaptation and the intergenerational transmission of cultural practices within local diasporic communities. Methodologically, the demographic portrait provides a foundation for future sampling strategies and mixed‑method research. Practically, it informs local images by identifying the types of social and linguistic support most relevant to this population. The results are preliminary but offer valuable insights for understanding regional migration dynamics and planning further large‑scale studies.